High negative predictive value of a normal faecal calprotectin in patients with symptomatic intestinal disease. Issue 1 (19th September 2011) - Turvill, James
Abstract : Background: Calprotectin is a heat stable intracellular protein shed by neutrophils into the intestinal lumen in response to inflammation. Lack of specificity makes its role in the assessment of inflammatory bowel disease uncertain. However, the strength of faecal calprotectin testing may lie in its negative predictive value (NPV) rather than positive predictive value (PPV) of organic intestinal disease. Objectives: To determine whether a normal faecal calprotectin in new patients with symptoms safely predicts for functional intestinal disease. Methods: To determine the predictive values of normal and raised faecal calprotectin by retrospective review of outcomes in consecutive primary care referrals into secondary care. Patients aged 16–60 years (mean age 41 years; 70% female patients) with intestinal symptoms were identified. 500 referrals had a normal faecal calprotectin and 130 had a raised result. 'Fast track' referrals were excluded. Outcome measures were the NPV of a normal faecal calprotectin and PPV of a raised faecal calprotectin. Results: Normal faecal calprotectin had an NPV of 0.964 for excluding symptomatic organic intestinal disease. Significant incidental non-intestinal (3.6%) and intestinal (6.4%) diseases were also identified. Mean follow-up was 4.8 years with no diagnostic revisions. In the raised faecal calprotectin cohort, the PPV for organic intestinal disease was 0.7. Conclusions: A normal faecal calprotectin safely predicts for functional intestinal disease. It may represent a powerful screening tool for excluding organic intestinal disease in primary care. A prospective primary care based study is needed.